2013
DOI: 10.1128/jb.01442-12
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Alkyl Gallates against Xanthomonas citri subsp. citri

Abstract: The plant-pathogenic bacterium Xanthomonas citri subsp. citri is the causal agent of Asiatic citrus canker, a serious disease that affects all the cultivars of citrus in subtropical citrus-producing areas worldwide. There is no curative treatment for citrus canker; thus, the eradication of infected plants constitutes the only effective control of the spread of X. citri subsp. citri. Since the eradication program in the state of São Paulo, Brazil, is under threat, there is a clear risk of X. citri subsp. citri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(130 citation statements)
references
References 46 publications
5
117
1
1
Order By: Relevance
“…Here, we further characterized the Xac mutant strain used by Silva et al. () that is labeled for the centromere (Xac parB ::pAPU3), and extended the studies with ParB encoded by this plant pathogen. First, we showed that Xac ParB is stably expressed and operates on chromosome segregation.…”
Section: Discussionmentioning
confidence: 89%
“…Here, we further characterized the Xac mutant strain used by Silva et al. () that is labeled for the centromere (Xac parB ::pAPU3), and extended the studies with ParB encoded by this plant pathogen. First, we showed that Xac ParB is stably expressed and operates on chromosome segregation.…”
Section: Discussionmentioning
confidence: 89%
“…The antibacterial activity of the compounds was evaluated using the Resazurin Microtiter Assay Plate (REMA) adapted to X. citri (Silva et al., ). Compounds, as dried powders, were diluted in 100% DMSO to a starting concentration of 10 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The nisin, nisin variants, and other lantibiotics used in this study all displayed antibacterial activity against B. subtilis (Table 1), as determined using the resazurin microplate assay (REMA), which uses the resazurin-resorufin dye pair to assess the metabolic capacity of cells (15) (see the methods in the supplemental material). The MIC 50 s determined correspond well with MIC values reported in the literature for the various compounds (8,(16)(17)(18).…”
mentioning
confidence: 99%